Synthesis and biological evaluation of cyclopeptide GG-8-6 and its analogues as anti-hepatocellular carcinoma agents. Issue 3 (1st February 2018) - Chen, Jie-Tao; Ma, Ru; Sun, Shi-Chang; Zhu, Xiao-Feng; Xu, Xiao-Li; Mu, Qing
Graphical abstract: Abstract: GG-8-6, cyclo-(Val-Leu-Pro-Ile-Leu-Leu-Leu-Val-Leu, compound 1 ), and its twelve analogues (compound 2 –13 ) were synthesized based on the lead compound Grifficyclocin B, a cyclic peptide with anti-tumor activity which was isolated from the plants of Goniothalamus species (Annonaceae). The bioassay results showed that these synthetic cyclopeptides exhibited different extent of cytotoxicity against human hepatocellular carcinoma cell lines. Among them, GG-8-6 (1 ) was the most active compound with IC50 values of 6.38 μM and 12.22 μM against SMMC-7721 and HepG2, respectively. Further studies on the mechanism demonstrated that GG-8-6 (1 ) could induce apoptosis and G2/M arrest of HCC cells, and the activation of caspase pathways was probably involved. In vivo anti-tumor experiments showed that GG-8-6 (1 ) could significantly inhibit the growth of tumor in the mouse xenograft tumor model. At the dose of 40 mg/kg, the inhibition ratio was 67.9% without weight loss. Our results suggested that GG-8-6 (1 ), a new cyclic peptide, might be a potential candidate for developing new anti-HCC drug in the coming future.